Association Between Respiratory Infections and Risk of Autism Spectrum Disorder: An Overview - Turriziani, Laura; Mancini, Arianna; Midiri, Maria; Albertini, Maria Ludovica; Butera, Ambra (Current Respiratory Medicine Reviews, 2025)
Autism Spectrum Disorder (ASD) is a complex and heterogeneous neurodevelopmental disorder. Its incidence has dramatically risen during the last few decades. ASD is a multifactorial disorder. In addition to genetic factors, the environment plays a key role during critical periods of neurodevelopment. The prenatal environment, as well as perinatal and postnatal exposures to infection and inflammation, are increasingly identified as potential risk factors for autism and can influence development and increase neurodevelopmental disorders. Immune dysfunction and dysregulation are considered an important factor contributing to the pathogenesis of autism and may influence the course and severity of the disease. This study aims to analyze the data available in the scientific literature regarding the correlation between respiratory infections and autism.
Keywords: vaccine